2012
DOI: 10.1134/s0022476612010143
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure investigation of Co(III) complex salts with the perrhenate anion

Abstract: Complex salts of the composition [Co(NH 3 ) 6 ](ReO 4 ) 3 ⋅2H 2 O (I), [Co(en) 3 ](ReO 4 ) 3 (II), [Co(NH 3 ) 5 H 2 O](ReO 4 ) 3 ⋅2H 2 O (III), and [Co(NH 3 ) 5 Cl](ReO 4 ) 2 ⋅0.5H 2 O (IV) are obtained. Their crystal structures are determined by single crystal XRD. Crystallographic characteristics: (I) a = 9.9797(3) Å, b = 12.6994(3) Å, c = 14.7415(4) Å, β = 102.870(1)°, C2/c space group; (II) a = 8.0615(3) Å, b = 8.4483(4) Å, c = 8.8267(4) Å, α = 61.923(2)°, β = 89.552(2)°, γ = 72.295(2)°, P1 space group; (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…In the tetrahedral [ReO 4 ] À anion in (I), the average Re-O bond length (1.719 Å ) is in agreement with the average Re-O bond length of 1.720 Å in [Co(NH 3 ) 6 ](ReO 4 )Á2H 2 O (Baidina et al, 2012). In (I) the values of three Re-O bond lengths, [Re1-O2 i , Re-O2 and Re-O2 ii = 1.715 (8) Å ; symmetry codes: The molecular structure of (I) showing displacement ellipsoids drawn at the 50% probability level for all non-H atoms.…”
Section: Structural Commentarysupporting
confidence: 71%
See 1 more Smart Citation
“…In the tetrahedral [ReO 4 ] À anion in (I), the average Re-O bond length (1.719 Å ) is in agreement with the average Re-O bond length of 1.720 Å in [Co(NH 3 ) 6 ](ReO 4 )Á2H 2 O (Baidina et al, 2012). In (I) the values of three Re-O bond lengths, [Re1-O2 i , Re-O2 and Re-O2 ii = 1.715 (8) Å ; symmetry codes: The molecular structure of (I) showing displacement ellipsoids drawn at the 50% probability level for all non-H atoms.…”
Section: Structural Commentarysupporting
confidence: 71%
“…The octahedral [Co(NH 3 ) 6 ] 3+ cation in (I) is slightly distorted; the average Co-N bond length of 1.962 Å is in agreement with the average Co-N bond lengths of 1.963 Å in [Co(NH 3 ) 6 ](ReO 4 )Á2H 2 O (Baidina et al, 2012) and 1.966 Å in [Co(NH 3 ) 6 ](TcO 4 ) 3 (Poineau et al, 2017). In (I), the shortest CoÁ Á ÁCo and NÁ Á ÁN separations between nearby [Co(NH 3 ) 6 ] 3+ cations are 7.035 (1) and 4.473 (1) Å , respectively.…”
Section: Structural Commentarysupporting
confidence: 67%
“…Unfortunately, this reaction route cannot be used to prepare compound 3-Mn due to the spontaneous reaction between the permanganate ions and the HCl solution (chlorine evolution and Mn II formation). Therefore, a chloride ion has to be introduced into the inner coordination sphere of the cobalt in the absence of a permanganate ion-for example, with the preparation of [Co(NH 3 ) 5 Cl]Cl 2 (compound 4) [14]-and the outer sphere chloride ions have to be exchanged with permanganate ions, such as occurred with the perrhenate ions in the preparation of compound 3-Re [15,16]. A possible reaction route is the reaction of [Co(NH 3 ) 5 Cl]SO 4 [14] with barium permanganate [17][18][19][20]; however, this method was not used due to the relatively low solubility of compound 3-Mn in water that causes problems in the separation of compound 3-M from the insoluble barium sulfate by-product.…”
Section: Synthesis and Properties Of Compound 3-mnmentioning
confidence: 99%
“…The powder X-ray diffractogram calculated from the SXRD data agreed very well with the experimentally determined powder X-ray diffractogram (Figure S1). Crystallographic data, details of the structure and the refinement results are listed in Table 2, together with the data obtained for the analog perrhenate complex (compound 3-Re) [15]. The structural features of compound 3-Mn are shown in Figures 1-3.…”
Section: Structure Of Compound 3-mnmentioning
confidence: 99%
“…It is found that synthesized [M(NH 3 ) 6 ](ReO 4 ) 3 ⋅2H 2 O (М = Ru, Ir) salts are isostructural to the previously studied phases with М = Со [22] and Rh [23]. Crystallographic data for the salts of this series are summarized in Table 1.…”
Section: Po mentioning
confidence: 72%